Beral et al's 1990 paper on Kaposi's sarcoma among persons with AIDS: demonstrating the power of descriptive epidemiology. (October 2016) - Newton, Robert; Whitby, Denise
Highlights: This paper provided much needed evidence of an underlying infectious cause for Kaposi's sarcoma. Incidence of KS was substantially higher among persons with AIDS than in the general population. Among those with AIDS, incidence was particularly high amongst men who have sex with men, suggesting possible routes of transmission. Abstract: Here we discuss the impact of Beral et al's 1990 paper "Kaposi's sarcoma among persons with AIDS: a sexually transmitted infection?" Not only did this paper galvanise research into the underlying infectious cause of Kaposi's sarcoma, it also demonstrated the power of observational epidemiology in pointing the way towards major discoveries.